(untitled) (XXI Century. Spanish Literature and Culture, 2003)
Despite its good fit with life’s speed, typical of the nineteenth century, the novella and the short-story are not genres which are too read. The genius of these genres lies in the briefness and intensity in which they display the plot and characters, leaving it to the reader to discover the details hidden between the lines.